The Image of City as Seen through Social Media Photographs: A Case Study of the Historical Context of Tabriz - Mahsa Chizfahm Daneshmandian; Morteza Mirgholami; Abbas Ghafari; Yaser Shahbazi (توسعه پایدار شهری)
The image of a city comprises the beliefs, perceptions, and imaginations that citizens hold about their city. These mental images provide a framework for urban planners to propose better futures for the city. In traditional urban planning approaches, this images were typically studied through interviews and cognitive mapping – time consuming, costly methods limited to small samples of citizens. However, today, social media and other digital technologies have provided new opportunities to study urban mental imagery. This research, seizing this opportunity, aims to explore the potential of social media visual data to study image of the city. To do so, a three-phase content analysis categorized 4,919 Instagram image data from the historical fabric of Tabriz. Kernel density estimation then mapped the data. Results demonstrate that images shared on social media can not only represent the perceived cognitive maps, but also provide more comprehensive analysis compared to classical methods. In addition to the physical dimensions of space, these data have the ability to represent non-physical dimensions such as environmental preferences, identity elements, activities, behaviors, cultural events, and beliefs of the society. They also enable remote measurement of mental images of the city at any scale, with minimal time and cost. Thus, social media-based urban images can be a valuable complement to classical methods of analyzing the mental image of cities. The analytical framework developed from this study can be used to evaluate and develop the classical theory of the mage of the city in the digital age.